Internationalization in Higher Education: an Analysis of Croatian Universities - Lenard, Dragana Božic; Lenard, Ivan (IJECA (International Journal of Education and Curriculum Application), 2023)
Around the globe, non-anglophone universities and higher education institutions (HEIs) are trying to internationalize providing students with opportunities to take non-language courses in a foreign language. The usual medium of instruction is English (EMI), which has become a global phenomenon. This paper aims to examine a macro-level university and HEIs’ policy on implementing non-language courses in four largest and oldest Croatian universities and their constituent units. Examining public records of the universities and HEIs, this study will research types and levels of study programs, operationalization of language medium instruction, policy implementation and curriculum evaluation. Since English/Language for Specific Purposes (ESP/LSP) courses can be perceived as preparatory courses for EMI/LMI, types, (non)obligatory nature and workload of ESP/LSP courses taught at the examined HEIs will be studied. The research showed that ESP courses are mostly taught as obligatory courses at the undergraduate level and occasionally as optional courses at the graduate study level. The highest workload of LSP courses is recorded at the HEIs from the Social Sciences fields and the lowest from the Natural Sciences fields, which consequently results in those HEIs (not) offering study programs in a foreign language.